2017
DOI: 10.1002/ana.24824
|View full text |Cite|
|
Sign up to set email alerts
|

Cerebral white matter abnormalities in patients with charcot‐marie‐tooth disease

Abstract: Here, we report the structural evidence of cerebral white matter abnormalities in Charcot-Marie-Tooth (CMT) patients and the relationship between these abnormalities and clinical disability. Brain diffusion tensor imaging (DTI) was performed in CMT patients with demyelinating (CMT1A/CMT1E), axonal (CMT2A/CMT2E), or intermediate (CMTX1/DI-CMT) peripheral neuropathy. Although all patients had normal brain magnetic resonance imaging, all genetic subgroups except CMT1A had abnormal DTI findings indicative of signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 20 publications
1
30
0
1
Order By: Relevance
“…However, rather surprisingly, no systematic study of conventional brain MRI on patients with CMTX has been reported to date. Recently, a diffusion tensor imaging study demonstrated white matter abnormalities in a series of 11 patients with GJB1 mutations 5. Interestingly, these abnormalities were limited to men, a finding only partly corroborated by present conventional MRI data, showing that callosal and diffuse white matter hyperintensity was more common in men than women.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, rather surprisingly, no systematic study of conventional brain MRI on patients with CMTX has been reported to date. Recently, a diffusion tensor imaging study demonstrated white matter abnormalities in a series of 11 patients with GJB1 mutations 5. Interestingly, these abnormalities were limited to men, a finding only partly corroborated by present conventional MRI data, showing that callosal and diffuse white matter hyperintensity was more common in men than women.…”
Section: Discussionmentioning
confidence: 53%
“…In the case of CMTX, subclinical CNS involvement, documented on brain MRI or evoked potentials, is not uncommon 6 7. This usually takes the form of transient confluent symmetric white matter lesions (WML) with posterior predominance on T2 MRI sequences, but can also be detected as more permanent diffusor tensor imaging abnormalities 5. Less commonly, clinical involvement ranging from extensor plantars to acute transient encephalopathy can be observed in patients with CMTX 7 8…”
Section: Introductionmentioning
confidence: 99%
“…This supports an important role for ER Ca 2+ in the pathogenesis of CMT1A, although any role disrupted by PMP mutations would likely be associated with Schwann cells and not with neuronal ER. The peripheral neuropathy CMT2A affects the peripheral and central nervous system, resulting in axon degeneration and progressive sensory loss in patients (Lee et al, 2017). CMT2A occurs as mostly autosomal dominant (Züchner et al, 2004), but sometimes recessive (Iapadre et al, 2018) or semi-dominant (Piscosquito et al, 2015) due to mutations in MFN2.…”
Section: Peripheral Neuropathies and Ermentioning
confidence: 99%
“…Some patients show additional symptoms such as hearing loss and scoliosis [ 8 ]. Interestingly, there are accumulating case reports of cerebral white matter abnormalities mainly in X-linked CMT type 1, and recently, abnormal diffusion-tensor imaging on brain MRI was shown to correlate with clinical disability in various CMT subgroups, suggesting subclinical central nervous system involvement in addition to clinical peripheral neuropathy [ 9 , 10 , 11 ]. Most patients develop symptoms in childhood, while there are marked individual differences in the severity and progression rate even in those with the same genetic alteration [ 12 ].…”
Section: Introductionmentioning
confidence: 99%